A preliminary study of the immunogenic response of plant-derived multi-epitopic peptide vaccine candidate of Mycoplasma gallisepticum in chickens - Mugunthan, Susithra Priyadarhni; Venkatesan, Divyadharshini; Govindasamy, Chandramohan; Selvaraj, Dhivya; Mani Chandra, Harish (Frontiers in Plant Science, 2024)
Mycoplasma gallisepticum (MG) is responsible for chronic respiratory disease in avian species, characterized by symptoms like respiratory rales and coughing. Existing vaccines for MG have limited efficacy and require multiple doses. Certain MG cytoadherence proteins (GapA, CrmA, PlpA, and Hlp3) play a crucial role in the pathogen's respiratory tract colonization and infection. Plant-based proteins and therapeutics have gained attention due to their safety and efficiency. In this study, we designed a 21.4 kDa multi-epitope peptide vaccine (MEPV) using immunogenic segments from cytoadherence proteins. The MEPV's effectiveness was verified through computational simulations. We then cloned the MEPV, introduced it into the plant expression vector pSiM24-eGFP, and expressed it in Nicotiana benthamiana leaves. The plant-produced MEPV proved to be immunogenic when administered intramuscularly to chickens. It significantly boosted the production of IgY neutralizing antibodies against cytoadherence protein epitopes in immunized chickens compared to the control group. This preliminary investigation demonstrates that the plantderived MEPV is proficient in triggering an immune response in chickens. To establish an efficient poultry health management system and ensure the sustainability of the poultry industry, further research is needed to develop avian vaccines using plant biotechnology.